Manajemen Pembelajaran Dalam Meningkatkan Kualitas Pembelajaran Peserta Didik - Dimas Zuhri Ahmad; Rika Handayani; Farah Diba; Meitha Maulina (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine and analyze the management of learning strategies applied in SD Islam Modern Darunnajah Serang in improving the quality of learning. This research uses a qualitative approach with a case study method. The subjects of the study were principals, vice principals for curriculum, teachers, and students. Data collection techniques use interviews, observation, and documentation. The results showed that the management of learning strategies applied at SD Islam Modern Darunnajah Serang includes five aspects, namely: (1) planning, which includes setting goals, indicators, and learning strategies; (2) organizing, which includes task distribution, coordination, and resource allocation; (3) implementation, which includes the application of learning models, methods, and media; and (4) supervision, which includes monitoring, evaluation, and follow-up. The management of learning strategies applied at SD Islam Modern Darunnajah Serang has succeeded in improving the quality of learning as shown by the achievement of learning quality indicators, such as student learning outcomes, student activeness, parental involvement, student satisfaction, and school achievement.